New 'ndrangheta territories. The case of Reggio Emilia. (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
‘Ndrangheta is a 30-year phenomenon in Reggio Emilia. This article aims to inquire   the fundamental steps of its development, identifying the structural features of the organization and analysing its spread within the socio-economic context. Moreover, this essay focuses on the role of cooperative ventures in the key sectors of mafia’s investments. The main findings put into light many links between mafia enterprises and Emilian cooperative system.Keywords: mafia, ‘ndrangheta, economy, Reggio Emilia, cooperative venture